Fabrication of Graphene Oxide Reinforced Bio‐Nanocomposite Films with Antibacterial Potential. Issue 1 (23rd February 2023) - Das, Mamata; Panda, Rupayana; Ray, Lipsa; Sethy, Chinmayee; Kundu, Chanakya Nath; Tripathy, Jasaswini
Abstract: The antimicrobial properties of graphene oxide (GO) have triggered a strong interest in the development of GO‐based antimicrobial polymer nanocomposites. GO incorporated polyvinylpyrrolidone (PVP) and carboxymethyl cellulose (CMC) blend‐based polymer nanocomposites are developed for antibacterial applications. The successful synthesis of GO is confirmed by transmission electron microscopy while the fabrication of CMC/PVP blend and CMC/PVP/GO is confirmed through FT‐IR spectroscopy and X‐ray diffraction (XRD) analysis. The morphological characteristics of polymer nanocomposites are studied using scanning electron microscopy. The films are also characterized using energy dispersive spectroscopy (EDX) which reveals the successful inclusion of the GO sheets in the polymeric matrix. The antibacterial efficacy of polymeric nanocomposite is tested against Gram –ve bacterial strain ( Escherichia coli The CMC/PVP/GO nanocomposites exhibited inhibition of bacterial cell growth.